Whole-genome sequencing of multidrug-resistant Mycobacterium tuberculosis isolates from Myanmar. (September 2016) - Aung, Htin Lin; Tun, Thanda; Moradigaravand, Danesh; Köser, Claudio U.; Nyunt, Wint Wint; Aung, Si Thu; Lwin, Thandar; Thinn, Kyi Kyi; Crump, John A.; Parkhill, Julian; Peacock, Sharon J.; Cook, Gregory M.; et al.
Highlights: Drug-resistant tuberculosis (TB) is a major health threat in Myanmar. The first whole-genome sequencing study of drug-resistant TB from Myanmar. Introduction of second-line drug susceptibility testing as part of routine diagnosis in Myanmar is needed. Abstract: Drug-resistant tuberculosis (TB) is a major health threat in Myanmar. An initial study was conducted to explore the potential utility of whole-genome sequencing (WGS) for the diagnosis and management of drug-resistant TB in Myanmar. Fourteen multidrug-resistant Mycobacterium tuberculosis isolates were sequenced. Known resistance genes for a total of nine antibiotics commonly used in the treatment of drug-susceptible and multidrug-resistant TB (MDR-TB) in Myanmar were interrogated through WGS. All 14 isolates were MDR-TB, consistent with the results of phenotypic drug susceptibility testing (DST), and the Beijing lineage predominated. Based on the results of WGS, 9 of the 14 isolates were potentially resistant to at least one of the drugs used in the standard MDR-TB regimen but for which phenotypic DST is not conducted in Myanmar. This study highlights a need for the introduction of second-line DST as part of routine TB diagnosis in Myanmar as well as new classes of TB drugs to construct effective regimens.